Transformational dimensions of cyber crime - Sirohi, M. N. (Alpha Editions, 2015)
"Cybercrimes committed against persons include various crimes like transmission of child-pornography harassment of any one with the use of a computer such as email. The trafficking, distribution, posting and dissemination of obscene material including pornography and indecent exposure, constitutes one of the most important cybercrimes known today. The worldwide information infrastructure is today increasingly under attack by cyber criminals and terrorists -- and the number, cost, and sophistication of the attacks are increasing at alarming rates. The challenge of controlling transnational cyber crime requires a full range of responses, including both voluntary and legally mandated cooperation This book makes an serious attempt to understand the Cyber Crime which involves activities like Credit Card Frauds, unauthorized excess to other's computer system, Pornography, Software piracy and Cyber stalking etc."--Back cover